Etika Komunikasi Islam dalam Kegiatan Pembelajaran Online - evy Septiana Rachman; Mat Jalil (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2020)
Corona Virus Disease or known as Covid 19 is a disease outbreak that has a profound impact on the lives of people around the world. No exception in Indonesia, all sectors of life such as education are a challenge that must be faced wisely. Educational institutions are required to be able to adapt to Covid 19 so that they are able to carry out educational functions so that they can continue to run optimally. However, in the implementation process, various kinds of obstacles were encountered, one of which was related to ethics in communicating between lecturers and students, which often caused miscommunication. The online learning process that is expected to be able to form good character and personality in accordance with educational goals is not able to be carried out optimally. If this is allowed to continue, it will lead to the failure of the purpose of education in shaping the character and personality of a generation that has good morals in accordance with Islamic teachings on how to communicate properly and correctly. Therefore it is necessary to apply Islamic communication ethics in online learning